Association of farmers' socio-economics with bovine brucellosis epidemiology in the dry zone of Sri Lanka - Kothalawala, K.A.C.; Makita, K.; Kothalawala, H.; Jiffry, A.M.; Kubota, S.; Kono, H. (Elsevier, 2017)
The aim of the study was to investigate the farmers’ socio-economic factors and their association with Brucella prevalence in the dry zone of Sri Lanka. A cross-sectional survey was planned and a total of 1,153 blood samples were collected from milking and dry animals of 155 farms from three selected veterinary ranges of Kalmunai, Navithanveli, and Mahaoya in the Ampara district, which is a multi-ethnic area. The Rose Bengal Test (RBT) and competitive enzyme-linked immunosorbent assay (c-ELISA) were used for the Brucella screening and confirmation, respectively. Socio-economic attributes such as family income, poverty, education, main job, ethnicity, parent farmer, farming experience, and training in animal husbandry were determined as potential farmer-level risk factors. Meanwhile, herd size, grazing practice, breeding method, animal brought-in to the farm, and abortions were considered as herd factors. The results revealed that the overall animal level sero-prevalence of brucellosis was 2.7% (35/1153; 95% confidence interval [CI]: 1.7, 3.7%) and the herd prevalence was 9.6% (15/155; 95% CI: 5.7, 15.7%) in the area of study. Brucellosis prevalence varies significantly (p < 0.001) among the selected veterinary ranges with the highest herd prevalence in Kalmunai (20.0%) followed by Navithanveli (11.9%) and Mahaoya (2.7%). Disease prevalence showed variability (p < 0.001) among ethnicities with the highest in Muslims (27.3%) followed by Tamils (8.1%) and Sinhalese (2.7%). Poverty was highly associated (OR = 3.75; 95% CI: 1.43-10.00) with the disease. Free movement grazing practices (p < 0.01) with OR = 7.2 and animal brought-in from outside (p < 0.06) with OR = 3.06 were positively related to brucellosis. It was revealed that farmers’ socio-economics, such as ethnicity and poverty, and animal movement patterns, such as grazing practices are significantly associated with epidemiology of brucellosis in the dry zone of Sri Lanka. Therefore, the “farmer factor” should be carefully considered in veterinary epidemiological studies and animal disease control plans in the future.